Experiences on early age cracking of wall-on-slab concrete structures - Jędrzejewska, Agnieszka (2020)
This paper is an effect of coordinated efforts of Working Group 7 of RILEM TC 254-CMS: Thermal cracking in massive concrete structures. The paper deals with a negative effect of restrained hardening-induced strains in reinforced concrete wall-on-slab structures which is cracks formed at the stage of construction of the walls. The aim of the paper was to collect real-life examples of wall-on-slab structures in which hardening-induced cracking was reported, and make a comparative study of these cases to observe patterns and trends on the cracking behaviour of such elements. The study covered a set of almost 20 cases with detailed material and technological data as well as observed cracking patterns. Characteristics of these structures which determine the capacity of crack development were indicated. In addition, for chosen cases the expected crack width was calculated and compared with the measured value. The calculations were performed with the use of current standardised guidance (EN 1992-3 and CIRIA C766) using an approach available at the design stage. This investigation showed that the method of CIRIA C766, being less conservative, consistently predicts smaller crack widths for a fixed set of assumptions compared to EN 1992-3, and both methods showed important discrepancies between the predicted and measured values of crack widths. Changes in calculation methods were proposed to improve the predictability of crack width calculations in wall-on-slab structures under restrained hardening-induced strains.